Response of Saos-2 osteoblast-like cells to kilohertz-resonance excitation in porous metallic scaffolds. (June 2020) - Deering, Joseph; Presas, Alexandre; Lee, Bryan E.J.; Valentin, David; Yu, Bosco; Heiss, Christian; Grandfield, Kathryn; Bosbach, Wolfram A.
Abstract: Post-operative therapy for joint replacement is often performed to optimize bone volume and bone-implant contact. Methods, such as pulsed therapeutic ultrasound, have been shown to be a valuable addition to regular physiotherapy to increase bone regeneration. To evaluate the efficacy of kilohertz-frequency (kHz) resonant stimuli to additively manufactured implant analogues, Saos-2 cells were seeded onto porous stainless steel scaffolds and flat substrates. Resonant frequency modes were mapped in the low kHz range, and cells were subjected to daily stimulus for 10 min at a frequency of 1.278 kHz. kHz-frequency excitation was found to increase normalized alkaline phosphatase production by almost twofold on metallic substrates relative to non-vibrated control scaffolds, while peak velocity influenced alkaline phosphatase production on porous scaffolds but not flat substrates. Total cell proliferation was downregulated by excitation, and all excited samples displayed larger variability. This work indicates that vibration within the range of 0.16–0.48 mm/s may reduce cell proliferation, but favour osteogenic gene expression. This study highlights the potential of using kHz-resonance therapy to mitigate early-onset pore occlusion to achieve uniform osseointegration through porous metallic scaffolds. Graphical abstract: Image 1